Connotative-Estimated Potential of Words - Representatives of Concept of RUSSIANNESS in Modern Russian Language - N. G. Glebova (Научный диалог)
The possibilities of words representing the concept of RUSSIANNESS to express positive-evaluative or negative-evaluative meanings are covered. The purpose of the study is to describe the linguistic mechanisms leading to positive and / or negative connotative evaluative background behind the usage of semantic word-formational derivatives - representatives of the concept of RUSSIANNESS in the modern Russian language. The research material are the language data of the main explanatory and word-formation dictionaries of the Russian language. The study is based on the methodological foundations of analysis of “language of the national culture” and theoretical principles of studying connotative evaluative component of the national concept sphere. The study uses the methodology for the analysis of the concepts developed in the works of scholars of Lobachevsky State University. Figurative meanings of the noun and adjective russkiy ‘Russian,’ with evaluative connotations, as well as derivatives rusak / rusachka , rusopyat , obruset’ / obrusit’ , rusifitsirovat’ , rusofil , rusofob , psevdorusskiy , antirusskiy are explored. The conclusion is that these words have significant positive or negative connotative-evaluative potential, expressing axiologically significant opposition along the lines of “own” - “alien” that allows to use it in the representation of national auto- and heterostereotypes in the discourses of different types, including demagogic or manipulative purposes. The practical importance of research consists in possibility to apply its results in political speechwriting, journalism, PR and advertising practice, as well as in judicial and non-judicial linguistic expertise in the field of extremism.